Quantum transport in nanostructured thermoelectric generator - Hossain, Mohammad Mobassar; Uzzaman, Md. Sharif; Ahmed, Shabab Azfar; Shafat, Md. Shahriar (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016.